Studying of deformation effect on energy levels in heavy nuclei region - Qaissar Abdulhussein Abbas; Heiyam Najy Alkhafajy (Al-Qadisiyah Journal of Pure Science, 2018)
The work aims to study nuclear structure for some heavy nuclei Using the first interacting bosons model (IBM-1) and it calculated low-lying structure levels To determine the type of dynamic symmetry that those isotones belongs to it (178Yb, 180Hf, 182W, 184Os ) It has been predicted angular momentum and parity for some energy levels that have not been a definite to be a specific has been confirmed each other and find the momentum and symmetry of some of the other not previously denitrified practically